Adaptive Identification of Nonlinear Time-delay Systems Using Output Measurements⁎The research were developed under support of RSF (grant 18-79-10104) in IPME RAS. Issue 2 (2020) - Furtat, Igor; Orlov, Yury
Abstract: A novel adaptive identifier is developed for nonlinear time-delay systems composed of linear, Lipschitz and non-Lipschitz components. To begin with, an identifier is designed for uncertain systems with a priori known delay values, and then it is generalized for systems with unknown delay values. The algorithm ensures the asymptotic parameter estimation and state observation by using gradient algorithms. The unknown delays and plant parameters are estimated by using a special equivalent extension of the plant equation. The algorithms stability is presented by solvability of linear matrix inequalities.